Education at the frontier between tradition and innovation: challenges of an international initiative in breaking through - Altıok, Birce; Conti, Luisa (Frontiers in Sociology, 2024)
In a rapidly evolving global landscape, education stands as a linchpin for navigating complex challenges and fostering sustainable development. This article delves into the transformative potential of education, with a particular focus on insights gleaned from the KIDS4ALLL project. Rooted in contrasting perspectives of education, the study emphasizes the need for a paradigm shift toward fostering critical thinking, creativity, and inclusivity. The European Commission’s commitment to transformative education finds expression in initiatives like KIDS4ALLL, which harnesses digital platforms to prioritize peer learning and bridge divides. Through an exploration of reactions within Turkish schools to the project’s introduction, this study sheds light on the dynamics of change and resistance, offering valuable insights into the challenges and opportunities towards educational transformation. Drawing on empirical data from the project’s pilot phase, the study identifies key factors shaping the realization of educational change. By elucidating these factors, the article contributes to a nuanced understanding of transformative education, paving the way for informed strategies aimed at fostering inclusive, sustainable, and impactful educational practices on a global scale.